The governance of public special schools in the Western Cape : a comparative analysis of Jan Kriel School and Thembalethu ELSEN School - Jonas, Patrick Thando (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2005.